Kinesiophobia and associated factors among patients after cardiac surgery under cardiopulmonary bypass: a cross-sectional study - You, Min; Mou, Qianqian; Cao, Xiaotao; Luo, Meng; Song, Yi; Li, Qingqing; Hu, Huiyun; Song, Jianping (Frontiers in Psychiatry, 2025)
BackgroundKinesiophobia is a significant psychological factor that affects the early ambulation of postoperative patients, and is especially prevalent among postoperative cardiac patients. Nonetheless, few studies have explored this phenomenon in patients following cardiac surgery under cardiopulmonary bypass.ObjectivesThe primary objective of this study was to investigate the prevalence of kinesiophobia and its contributing factors in patients after cardiac surgery under cardiopulmonary bypass, to inform the development of targeted intervention strategies to address kinesiophobia, enhance patient motivation and adherence to early activities, and optimize postoperative rehabilitation outcomes.MethodsA cross-sectional survey was conducted, assessing patients via questionnaires, including the Tampa Scale for Kinesiophobia Heart, Exercise Self-Efficacy Scale, D Personality Scale-14, Pain Catastrophizing Scale, and Family Care Index Questionnaire. The χ2 test, Fisher’s exact test, and Mann-Whitney U test were used for univariate analysis, and binary Logistic stepwise regression analysis was adopted for multivariate analysis. The difference was considered statistically significant at P<0.05.ResultsThe study encompassed a total of 293 patients, of whom 45.73% (134 patients) exhibited kinesiophobia. Binary logistic regression identified the following risk factors: being accompanied by a nursing assistant (OR = 9.009, P < 0.001), longer cardiopulmonary bypass duration (OR = 1.005, P < 0.05), delayed first postoperative ambulation (OR = 4.031, P < 0.05), Type D personality (OR = 2.582, P < 0.01), heightened safety concerns (OR = 8.270, P < 0.05), and pain catastrophizing (OR = 4.253, P < 0.001). Conversely, family function and exercise self-efficacy mitigated kinesiophobia (P < 0.05).ConclusionsKinesiophobia is highly prevalent and multifactorial in post-cardiopulmonary bypass patients. Healthcare providers should prioritize patients with the above risk profiles, while also establishing financial/emotional support systems, improving patient-family communication, optimizing acute pain management, implementing Enhanced Recovery After Cardiac Surgery protocols, and leveraging technology to design rehabilitation programs. These measures may reduce kinesiophobia and maximize the benefits of early ambulation.